Opinion of the Scientific Committee on health, environmental and emerging risks on the safety of titanium dioxide in toys - Theo G. Vermeire; Peter Hoet; Rodica-Mariana Ion; Renate Krätke; Ana Proykova; Marian Scott; Wim H. de Jong; Laurent Bodin; Maria Dusinska; Maciej Stepnik; Susan W.P. Wijnhoven; Herman Autrup; et al. (Regulatory Toxicology and Pharmacology, 2024)

Exposure to airborne iron oxide nanoparticles induces oxidative DNA damage and inflammatory responses: a pilot study in welders and in human lung epithelial cell line - Chatchai Thanachoksawang; Panida Navasumrit; Potchanee Hunsonti; Chalida Chompoobut; Krittinee Chaisatra; Herman Autrup; Mathuros Ruchirawat (Toxicology and Environmental Health Sciences, 2022)

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

Cytotoxicity and genotoxicity of silver nanoparticles in the human lung cancer cell line, A549 - Rasmus Foldbjerg; Duy Anh Dang; Herman Autrup (Archives of Toxicology, 2011)

Limit-test toxicity screening of selected inorganic nanoparticles to the earthworm Eisenia fetida - Lars-Henrik Heckmann; Mads B. Hovgaard; Duncan S. Sutherland; Herman Autrup; Flemming Besenbacher; Janeck J. Scott-Fordsmand (Ecotoxicology, 2011)

Toxicological comments to the discussion about REACH - Helmut Greim; Michael Arand; Herman Autrup; Hermann M. Bolt; James Bridges; Erik Dybing; Rémi Glomot; Vito Foa; Rolf Schulte-Hermann (Archives of Toxicology, 2006)

Dietary elevated sucrose modulation of diesel-induced genotoxicity in the colon and liver of Big Blue rats - Lotte Risom; Peter Mller; Max Hansen; Herman Autrup; Jette Bornholdt; Ulla Vogel; Hkan Wallin; Henrik E. Poulsen; Lars O. Dragsted; Steffen Loft (Archives of Toxicology, 2003)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Inhibition of intercellular communication by condensates of high and low tar cigarettes - Ole Vang; Håkan Wallin; Herman Autrup (Archives of Toxicology, 1995)